ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PENGRAJIN SANDAL SAAT PANDEMI - Fidha Shafira; Farida Rahmawati (Jurnal Ekonomi dan Bisnis (EK&BI), 2021)
The COVID pandemic has infected almost all countries in the world and caused a high number of deaths. One of the steps taken by the government to break the chain of spread of COVID in the community is to implement physical distancing as recommended by the World Health Organization (WHO). This policy has negative consequences for various things, including those related to business so that businessmen cannot carry out their activities properly. Restrictions on movement and activity during this pandemic have disrupted supply chains which can cause an imbalance in production factors, and lead to a decrease in demand. The purpose of this study was to analyze the effect of capital, labor, and length of business on the production and income of sponge sandal craftsmen during a pandemic at the sponge sandal craft industry center in Toyomarto Village, Malang Regency. The number of samples used were 36 industrial units. The analytical technique used is path analysis. The results showed that capital and labor had a positive and significant effect on production and income, while length of business had a negative and significant effect on the production and income of sponge sandal craftsmen during a pandemic.